1981
DOI: 10.1083/jcb.91.2.427
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of alveolar wall basement membrane in the adult rat lung.

Abstract: The ultrastructural characteristics of alveolar (ABM) and capillary (CBM) basement membranes in the adult rat lung have been defined using tannic acid fixation, ruthenium red staining, or incubation in guanidine HCI. ABM is dense and amorphous, has 3-to 5-nm filaments in the lamina rara externa (facing the alveolus) that run between the lamina densa and the basal cell surface of the epithelium, has an orderly array of ruthenium red-positive anionic sites that appear predominantly (79%) on the lamina rara exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(68 citation statements)
references
References 41 publications
1
66
0
1
Order By: Relevance
“…Based on selective enzyme degradation, ruthenium red appears to react with heparan sulfate proteoglycan, and the LRI of the adult rat lung has one-fifth the number of ruthenium red anionic binding sites compared with the LRE. Interestingly, this difference is not observed in neonatal rats; hence, the diminished reactivity of the LRI appears to be an age-acquired phenotype (26,264,265). In the ABM of adult rats and rabbits, differences in microdomains between type I and II cells have been reported.…”
Section: B Extracellular Matrix Of the Alveolar Wallmentioning
confidence: 96%
See 2 more Smart Citations
“…Based on selective enzyme degradation, ruthenium red appears to react with heparan sulfate proteoglycan, and the LRI of the adult rat lung has one-fifth the number of ruthenium red anionic binding sites compared with the LRE. Interestingly, this difference is not observed in neonatal rats; hence, the diminished reactivity of the LRI appears to be an age-acquired phenotype (26,264,265). In the ABM of adult rats and rabbits, differences in microdomains between type I and II cells have been reported.…”
Section: B Extracellular Matrix Of the Alveolar Wallmentioning
confidence: 96%
“…Several other studies (2,26,265) demonstrated discontinuities in the basement membranes of rat type II pneumocytes through which extensions of cytoplasm contact interstitial fibroblasts. Through morphometric analysis they estimated these contacts occur with a frequency of 0.5 and 0.7 per pneumocyte, respectively.…”
Section: Fibroblasts: a Source Of Contact Guidance And Stimulatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Alveolar basal lamina consists of numerous anionic (negatively charged) sites that contain heparan sulfate proteoglycans [83]. The heparin sulfate proteoglycan family includes, among others, collagen XVIII, which is abundant in the lung, although less than collagen IV [84].…”
Section: Normal Rage Expression Suppressed Rage Expressionmentioning
confidence: 99%
“…A close association between erythrocytes and endothelial cells was often seen in the peripheral regions of the alveoli. It may reflect intercellular communications during gas\material exchanges through a very narrow basement membrane (Groniowski & Biczysko, 1964 ;Voccaro & Brody, 1981).…”
Section: mentioning
confidence: 99%